2018
DOI: 10.1029/2017tc004895
|View full text |Cite
|
Sign up to set email alerts
|

Common Reflection Surface Stack Imaging of the Proterozoic Chambal Valley Vindhyan Basin and Its Boundary Fault in the Northwest India: Constraints on Crustal Evolution and Basin Formation

Abstract: The Vindhyan basin of northwestern and central India is one of the largest undeformed Meso-Neoproterozoic basins in the world with likely potential of hydrocarbons. Crustal seismic reflection data along a 165-km long Chandli-Bundi-Kota-Kunjer profile of the Chambal Valley Vindhyan basin processed using common reflection surface stack method brought out new crustal features, which were missing in earlier images. A gently dipping structure of the basin is imaged with a maximum of 7.5-km thick Proterozoic sedimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 68 publications
(97 reference statements)
0
11
0
Order By: Relevance
“… 2000 ; Mandal et al . 2018 ). Deep seismic reflection images of the region along the Nagaur–Jhalawar profile that runs perpendicular to the strike of the ADFB clearly identify structural features such as the west-dipping Jahazpur Thrust and the Great Boundary fault that extend through the entire crust (Vijaya Rao et al .…”
Section: Geology and Tectonicsmentioning
confidence: 99%
See 1 more Smart Citation
“… 2000 ; Mandal et al . 2018 ). Deep seismic reflection images of the region along the Nagaur–Jhalawar profile that runs perpendicular to the strike of the ADFB clearly identify structural features such as the west-dipping Jahazpur Thrust and the Great Boundary fault that extend through the entire crust (Vijaya Rao et al .…”
Section: Geology and Tectonicsmentioning
confidence: 99%
“… 2000 ; Mandal et al . 2018 ). The converging reflections within the ADFB and the presence of the ramp-flat structure of the Jahazpur Thrust confirm compression across the region (Vijaya Rao et al .…”
Section: Geology and Tectonicsmentioning
confidence: 99%
“…Then, the report of basaltic pillow lava from Mauranipur area in a subductionrelated tectonic setting of Archean age (Malaviya et al, 2006) and very high pressure metamorphism (up to 20 kb; Saha et al, 2011) from Babina area revolutionized the understanding of the BuC. The field and petrographic evidences are now very well supported by geophysical data (Gokarn et al, 2013;Mandal et al, 2018;Nabakumar and Kumar, 2018) indicating the existence of the BTZ. The Bouguer gravity anomaly map of the Bundelkhand Craton clearly divides the craton into a gravity low (Southern BuC) and relatively gravity high (northern BuC) domains on either side of BTZ (Fig.…”
Section: Geodynamic Evolution In Space and Timementioning
confidence: 93%
“…The decades of study, although under debate and inconclusive, have projected widely varying tectonic models extending from an intracratonic setting (Chanda & Bhattacharyya, 1982;Soni et al 1987), to a foreland setting (Chakraborty & Bhattacharyya, 1996;Chakrabarti et al 2007;Shukla et al 2019) to a temporarily evolved rift-sag setting (Sarkar et al 1995;Bose et al 1997Bose et al , 2001Sarkar et al 2002b). In particular, trace-element data, Nd isotope-based studies and seismic reflection studies (Chakrabarti et al 2007;Mandal et al 2018;Shukla et al 2019) speculate on the initiation of the Vindhyan basin as a foreland basin with the existence of a subduction-related arc system. Interestingly, proponents of a foreland setting differ in their subduction model.…”
Section: B Clues About Basin Tectonicsmentioning
confidence: 99%
“…Interestingly, proponents of a foreland setting differ in their subduction model. Chakrabarti et al (2007) and Shukla et al (2019) conceived subduction of the Bundelkhand craton under the Bastar and Aravalli cratons; however, from consideration of seismic reflection stack imaging, Mandal et al (2018) suggested the opening of the Vindhyan Basin in an extensional strike-slip mode that followed subduction and collision between the Bundelkhand craton and the Mewar craton. However, none of these studies supported their claims with field-based documentation such as the basin-scale variation in stratigraphic thickness of different formations and the pervasive northwesterly palaeocurrent from different stratigraphic levels of the Vindhyan succession present in the Son valley.…”
Section: B Clues About Basin Tectonicsmentioning
confidence: 99%